Hong Kong - A High Density City into an Era of Sustainability - Chan-Yi, Corrin Chan (MAJ - Malaysia Architectural Journal, 2025)
Hong Kong- A High Density City into an Era Sustainability; Hong Kong is one of the most dense city in the world, with a population of 7.413 million in 2024 people in the small area of 1,104- square-kilometre. The density of living is made more acute with only 23% of the land on buildable area. Yet High Density Living does not imply the sacrifice of Liveability, Sustainability and the well-being of People and the Environment. Hong Kong has been a city under pressure since its time of being a British Colony. The sudden growth in population in 1950s has caused tremendous pressure to the city to with the increased population in a very short time. High Density Living has always been the challenge to Hong Kong. And, at the same time, creative responsive solutions have appeared in the growth of the city and the manifestation of its own unique Architecture. The paper will present the city’s experience and ingenious solutions to the challenges of this era: High Density for Sustainability. The paper will be include the narrative of a super-dense urban city, Hong Kong as a 4-D condensed compact city, Changes in Government Policy in Sustainability, endeavours and emerging new movements for Hong Kong in the era for Sustainability, the change and new movements in Urbanism will be illustrated by prominent architectural endeavours in Public and Private, Residential, Institutional and Revitalization Project.